2012
DOI: 10.3168/jds.2011-4621
|View full text |Cite
|
Sign up to set email alerts
|

Identification and diversity of bovine major histocompatibility complex class II haplotypes in Japanese Black and Holstein cattle in Japan

Abstract: Bovine leukocyte antigen (BoLA), the major histocompatibility complex of cattle, is one of the most polymorphic gene clusters. We genotyped a population of 109 Japanese Black and 39 Holstein cattle to analyze their BoLA class II haplotypes, BoLA-DRB3 locus, 5 BoLA-DQA loci, and 5 BoLA-DQB loci. We identified 26 previously reported DRB3 alleles, 22 previously reported and 3 new DQA alleles, and 24 previously reported and 6 new DQB alleles. A dendrogram was constructed based on the predicted amino acid sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 31 publications
(57 reference statements)
5
72
0
2
Order By: Relevance
“…Similarly, many studies have shown that BoLA class II allele frequencies differ between cattle breeds. For example, allele frequencies of the BoLA-DRB3 gene differ between Jersey, Holstein, Argentine Creole, Japanese Shorthorn, Brazilian dairy Gir, and four Japanese breeds (7)(8)(9)(10)(11)(12)(13)(14). Recently, a PCR sequence-based typing (SBT) method was used to genotype BoLA-DRB3, and it showed greater discriminatory power and precision than PCR-restriction fragment length polymorphism (RFLP) for estimating BoLA-DRB3 diversity in cattle breeds (15).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many studies have shown that BoLA class II allele frequencies differ between cattle breeds. For example, allele frequencies of the BoLA-DRB3 gene differ between Jersey, Holstein, Argentine Creole, Japanese Shorthorn, Brazilian dairy Gir, and four Japanese breeds (7)(8)(9)(10)(11)(12)(13)(14). Recently, a PCR sequence-based typing (SBT) method was used to genotype BoLA-DRB3, and it showed greater discriminatory power and precision than PCR-restriction fragment length polymorphism (RFLP) for estimating BoLA-DRB3 diversity in cattle breeds (15).…”
Section: Introductionmentioning
confidence: 99%
“…From this cluster, at least 61 BoLA DQA and 81 BoLA DQB alleles have been described and listed in the IPD-MHC database, and 56 different haplotypes were described in Japanese Black and Holstein cattle [35]. The high number of different alleles, both on the DR and DQ loci, suggests that DR and DQ molecules complement each other for the presentation of a broad spectrum of antigens in cattle.…”
Section: The Major Histocompatibility Complex In Cattlementioning
confidence: 99%
“…143,[147][148][149][150][151][152] BoLA-DRB3*0902 animals with LPL phenotype did not transmit the infection at herd level in natural conditions, 48 and under experimental conditions, it was necessary to inoculate a large volume of blood in order to infect sheep. 145,147 Furthermore, to date, the BoLA-DRB3*0902 allele has not been associated with susceptibility to other infectious agent, nor has it negatively affected production or reproduction traits.…”
Section: Control Of Blv Infection By Genetic Selection Of Resistant Cmentioning
confidence: 99%